2006
DOI: 10.1021/ja058030v
|View full text |Cite
|
Sign up to set email alerts
|

[Fe(bpym)(CN)4]-: A New Building Block for Designing Single-Chain Magnets

Abstract: We herein present the preparation, crystal structure, magnetic properties, and theoretical study of new heterobimetallic chains of formula {[Fe(III)(bpym)(CN4)]2M(II)(H2O)2}.6H2O [bpym = 2,2'-bipyrimidine; M = Zn (2), Co (3), Cu (4), and Mn (5)] which are obtained by using the building block PPh4[Fe(bpym)(CN)4].H2O (1) (PPh4+= tetraphenylphosphonium) as a ligand toward the fully solvated MII ions. The structure of complex 1 contains mononuclear [Fe(bpym)(CN)4]- anions. Compounds 2-5 are isostructural 4,2-ribbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
96
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(104 citation statements)
references
References 79 publications
6
96
0
2
Order By: Relevance
“…These features may suggest the presence of weak interchain AFM interactions, which can exert the observed effect on the ac susceptibility at low temperature. [28] As in 3, the interchain magnetic coupling can be propagated through p-p interaction between the pyridine rings of adjacent chains. Here the pyridine and carboxylate groups are nearly coplanar.…”
mentioning
confidence: 99%
“…These features may suggest the presence of weak interchain AFM interactions, which can exert the observed effect on the ac susceptibility at low temperature. [28] As in 3, the interchain magnetic coupling can be propagated through p-p interaction between the pyridine rings of adjacent chains. Here the pyridine and carboxylate groups are nearly coplanar.…”
mentioning
confidence: 99%
“…1,9,11 The magnetic properties of such 1D systems were theoretically predicted by Glauber in the 1960s: 12 At low temperature, the magnetization relaxes slowly with a relaxation time that follows an Arrhenius law s ¼ s 0 Áexp(D/k B T), and no phase transition to threedimensional (3D) magnetic long-range order occurs before the magnetization blockage. 10,13 Subsequently, several other compounds were shown to exhibit SCM behavior, 11,[14][15][16][17][18][19][20][21] with quantum effects influencing the magnetization dynamics at low temperatures. 22 In particular, several works [23][24][25] showed that the requirements necessary to observe Glauber dynamics-a strong Ising-like anisotropy and a very low ratio of interchain/intrachain magnetic exchange interactions-are fulfilled in [Dy(hfac) 3 {NIT(C 6 H 4 OPh)}] (in short DyPhOPh).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, based-on the symmetry of the magnetic orbitals from the magnetic point of view, it is possible to predict the nature of the magnetic exchange between the cyanide-bridged paramagnetic metal ions by using simple orbital models. Therefore, up to now, a large amount of cyanide-bridged magnetic complexes with divers structures from 0D cluster to 3D network and interesting magnetic properties, such as highest T C molecule-based materials, moleculebased photomagnets, spin crossover materials, single-molecule magnets (SMMs), and single-chain magnets (SCMs), [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] have been successfully synthesized, structurally characterized and magnetically investigated.…”
Section: Introductionmentioning
confidence: 99%